MRI in the pre operative evaluation of perianal fistula - Rehman, Imaad ur; Akhtar, Samina; Rana, Atif; Latif, Uzair; Saleem, Hassan; Chaudhary, Miohammad Yousuf (Journal of Postgraduate Medical Institute, 2014)
Objective: To assess the diagnostic accuracy of Magnetic Resonance Imaging (MRI) in the pre operative evaluation of peri anal fistulae. Methodology: Between Decemebr 2010 and January 2013, thirty patients with clinical suspicion of peri-anal fistulae had MRI scans done for evaluation of extent of disease. Out of these 11 patients underwent surgery in our hospital and were included in the study. All patients had body-coil MR Imaging examinations including the following sequences for anatomic and pathologic information: T2 sagittal, T1, T2 and STIR axial oblique, T2 and STIR coronal oblique and post contrast T1 FAT SAT sagittal, axial oblique and coronal oblique planes. Scans were interpreted by a senior radiologist with more than 5 year experience in body MR imaging. Surgical findings were accepted =as the gold standard and were recorded independently by the surgeon. MRI findings were compared with surgical findings using Park's classification. Results: The MRI findings were in accordance with surgical findings in 10 out of 11 patients regarding type and extent of fistula in ano. In one patient peroperatively diagnosed and treated fistula did not show on MRI. Statistical parameters showed that MRI has a sensitivity of 90%, specificity of 100% and diagnostic accuracy of 90% in determining type and extent of peri-anal fistula. Conclusion: MRI is an accurate and non invasive imaging modality for determining type and extent of peri-anal fistula and helps in pre operative management and surgical planning by giving correct assessment of extent of disease. Key Words: .